Identify the Writing Ability of 5-6 Years Old (THUFULA, 2023)
This descriptive quantitative research is intended to observe the stimulation used and identify writing skills in children aged (5-6) years, then analyze according to the stages of writing development in children in PAUD Mentari Jaya, OKU Regency. With a total sample of 9 children. Data was collected through observation, interview and documentation techniques. Referring to previous research, data collection in this study used more complex instruments. The results showed that the children's writing ability was at a very well-developed stage, indicated by a score of 3.8 for holding a tripod grasp writing instrument. The ability to copy the cross marks a score of 3.7. The ability to copy triangular shapes gets a score of 3.6. A score of 3.3 for the ability to recognize between large and small curve lines. The ability to make scribbles such as shapes, marks, and directed lines gets a score of 3.4. A score of 3.3 for being able to write letters randomly to form a word. A score of 3.3 for the ability to distinguish similar letters. A score of 3.8 for the ability to trace simple writing. A score of 3.7 on the ability to copy simple text. And a 3.4 in the ability to write his name correctly. It was concluded that the writing ability based on the average score of each child and based on the ability of each indicator varied. Some indicators have developed well, and some still need further stimulation.